2020
DOI: 10.1017/s0376892920000405
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ perspectives and practices on biodiversity web portals as an opportunity to reconnect education with nature

Abstract: Summary Biodiversity loss is a complex issue and a risk that education cannot overlook. Teachers play a crucial role in how biodiversity, and in particular local biodiversity, is understood. To provide insight into how to improve communication on the subject, we investigate teachers’ perspectives and social representations regarding biodiversity, their fluency in terms of Internet use, their familiarity with biodiversity web portals and perceived pedagogical usefulness of technology. A sample of 243 K–12 sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…MS girls' greater preference for schemes C and E compared with MS boys may be explained by the particular emphasis placed by the former group on species richness. This finding agrees with several studies that revealed that biodiversity perspectives are still largely centered on species richness/diversity, neglecting other important dimensions of the concept [12,13,[21][22][23]. HS pupils' (of both genders) predilection for scheme F may be attributed to the importance attached to a natural colonization mode, and their greater knowledge and awareness of invasive species and associated threats compared with MS pupils.…”
Section: Pupils' Gender and School Level Influences Response Rates And Biodiversity Perspectivessupporting
confidence: 91%
See 3 more Smart Citations
“…MS girls' greater preference for schemes C and E compared with MS boys may be explained by the particular emphasis placed by the former group on species richness. This finding agrees with several studies that revealed that biodiversity perspectives are still largely centered on species richness/diversity, neglecting other important dimensions of the concept [12,13,[21][22][23]. HS pupils' (of both genders) predilection for scheme F may be attributed to the importance attached to a natural colonization mode, and their greater knowledge and awareness of invasive species and associated threats compared with MS pupils.…”
Section: Pupils' Gender and School Level Influences Response Rates And Biodiversity Perspectivessupporting
confidence: 91%
“…An example is the recently created subject "Azores History, Geography and Culture", starting in 2019-2020, that focuses, among other things, on local biodiversity and biological invasions [46]. As a result of changes in the formal Portuguese curriculum and the emergence of new educational approaches adopted by educators [22], among other factors, it is expected that Azorean pupils' biodiversity perspectives will have changed in the last nine years. However, how much they have changed and contributed to raising ecological literacy levels and engagement in environmental citizenship remains to be studied.…”
Section: Capturing Pupils' Perspectives About Ecological Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, an incomplete understanding of biodiversity has been acknowledged by previous studies. According to a study conducted in the Azores in Portugal [36], teachers' representations of biodiversity share some common points with the definition of the concept of biodiversity, although most focus only on the species dimension. A study of Dikmenli (2010), about the conceptual framework of biodiversity in 130 biology training teachers, shows that even if they had a more varied and technical vocabulary related to biodiversity, they still had an incomplete understanding of the concept.…”
Section: Teachers' Representations Of Biodiversitymentioning
confidence: 99%